The creative industries and international business development in Africa - Madichie, Nnamdi O.; Hinson, Robert Ebo (Emerald Publishing Limited, 2022)
The international business environment has undergone major turbulence in 2020 following the onset of lockdowns, travel restrictions and social distancing all prompted by Covid-19. These restrictions have limited the revenue generation capacity of both countries and businesses - large and small. While the winners have been mostly those sectors with a digital footprint such as streaming services and video-conferencing giants, the creative industries have felt a much harder blow. Against this backdrop, The Creative Industries and International Business Development in Africa takes an unorthodox approach to showcasing the trends and challenges of the contemporary creative economy with a view to positioning the sector for a global audience. Drawing upon the categorisations of the Creative Industries Federation, the book interrogates, and highlights, the challenges, and opportunities of the creative industries in Africa. This is with a view to aggregating how the sector has coped with a myriad of challenges even before the pandemic. Discussions across the chapters document the changing landscape of the sector, capturing insights from the global value chain to everything digital - from arts to publishing, fashion, film and music production and distribution. Further insights are discussed around recent events such as the take-off of the African Continental Free Trade Area (AfCFTA) and the exit of Britain from the EU - with the latter event reinvigorating the Commonwealth Agenda and renewed interest in Africa's creative industries.
Includes index.
Keywords: Cultural industries -- Africa.; International business enterprises -- Africa.; Africa -- Economic policy.; Africa -- Cultural policy.; Business & Economics -- Development -- Business Development.; International business.; elektronické knihy; electronic books